Pseudouridine Mapping in the Saccharomyces cerevisiae Spliceosomal U Small Nuclear RNAs (snRNAs) Reveals that Pseudouridine Synthase Pus1p Exhibits a Dual Substrate Specificity for U2 snRNA and tRNA - Massenet, Séverine (American Society for Microbiology, 1999)
Pseudouridine (Ψ) residues were localized in the Saccharomyces cerevisiae spliceosomal U small nuclear RNAs (UsnRNAs) by using the chemical mapping method. In contrast to vertebrate UsnRNAs, S. cerevisiae UsnRNAs contain only a few Ψ residues, which are located in segments involved in intermolecular RNA-RNA or RNA-protein interactions. At these positions, UsnRNAs are universally modified. When yeast mutants disrupted for one of the several pseudouridine synthase genes (PUS1, PUS2, PUS3, and PUS4) or depleted in rRNA-pseudouridine synthase Cbf5p were tested for UsnRNA Ψ content, only the loss of the Pus1p activity was found to affect Ψ formation in spliceosomal UsnRNAs. Indeed, Ψ(44) formation in U2 snRNA was abolished. By using purified Pus1p enzyme and in vitro-produced U2 snRNA, Pus1p is shown here to catalyze Ψ(44) formation in the S. cerevisiae U2 snRNA. Thus, Pus1p is the first UsnRNA pseudouridine synthase characterized so far which exhibits a dual substrate specificity, acting on both tRNAs and U2 snRNA. As depletion of rRNA-pseudouridine synthase Cbf5p had no effect on UsnRNA Ψ content, formation of Ψ residues in S. cerevisiae UsnRNAs is not dependent on the Cbf5p-snoRNA guided mechanism.